The Effect of Business Model Innovation, Customer Trust and Commitment on SME Business Growth - Shafira Firgynia Maharani; Zulian Yamit (CV. Publikasi Indonesia, 2022)
Business growth includes an increase in the number of turnover and an increase in the number of employees, which means if the business grows, its sales also increase. Efforts for SMEs to develop, the competitiveness of SMEs needs to be developed. Several factors can affect the growth of SMEs, so SMEs are required to innovate business models, increase trust, and commitment to customers in order to remain competitive with competitors out there. Due to the increasingly diverse needs of consumers, business people must also offer quality services so that consumers can feel comfortable. The primary purpose of this study was to determine the effect of business model innovation, customer trust, and customer commitment on SME business growth: a survey of the SME business at the Handicraft Center in Bantul. The population used in this research is the UKM craft center in Bantul. The sampling technique used in this research is purposive sampling. The sample used in this study amounted to 100 respondents. This study uses Structural Equation Modeling (SEM) analysis using the Partial Least Square (PLS) method. The results of this study indicate that business model innovation has a positive and significant effect on SME business growth, business model innovation through customer trust has a positive and insignificant impact on SME business growth, and business model innovation through customer commitment has a positive and significant impact on SME business growth.